The JWST early release science program for direct observations of exoplanetary systems: VI. Evidence for radially evolving icy grains in the HD 141569A disk via NIRCam coronagraphic imaging - Millar-Blanchaer, Maxwell; Choquet, Élodie; Lawson, Kellen; Marino, Sebastián; Kammerer, Jens; Carter, Aarynn L.; Rebollido, Isabel; Leisenring, Jarron M.; Kim, Minjae; Kalas, Paul; Stapelfeldt, Karl R; Hinkley, Sasha; et al. (The astrophysical journal, 2025)
We present JWST NIRCam coronagraphic observations of the HD 141569A circumstellar disk, obtained as part of the JWST Early Release Science program. The observations recover the multi-ringed structure seen in previous shorter-wavelength observations, but at filters centered on the ∼3 μm water ice absorption feature and a complementary continuum region (F300M and F360M, respectively). The observations reveal apparent absorption between the F300M and F360M filters that decreases with radius, with a notable change around 200 au, between the innermost and outermost two rings. These results are consistent whether the data is reduced via deconvolution or through a forward-modeling approach. We demonstrate that these changes suggest a radial decrease in the water ice mass fraction by a factor of ∼3-10 and possibly a change in minimum grain size. We do not detect any point sources within the system and can exclude planetary companions 2 Jupiter masses and greater beyond 1″ radius (∼111 au). These observations and the subsequent analysis illustrate a robust pathway for using JWST/NIRCam to characterize the distribution of water ice in other circumstellar disks. We highlight some of the early lessons learned from this work that we hope will be useful for future circumstellar disk observation planning and analysis.